THE EXISTENCE OF THE LEGAL POSITION OF OPINION BY STATE ATTORNEY AS A LEGAL SOURCE IN THE FRAMEWORK OF RESOLUTION OF LEGAL PROBLEMS - Ristanama, Yoga (Universitas Pendidikan Ganesha, 2025)
The public often relies on legal opinions provided by State Attorneys (JPN) or legal consultants as guidance in dealing with legal issues by using JPN (State Attorney) or legal consultants, where in the prosecutor's office there are also state attorneys who assist in conducting legal studies in resolving legal issues. The research method used by the author is a qualitative research method with a normative juridical approach. The research data was analyzed using content analysis. The results of the study indicate that in preparing a legal opinion, JPN (State Attorney) or a legal consultant must follow the guiding principles. Legal opinions are important for providing legal information based on strong law. The process of creating a legal opinion is carried out using a convergent approach, involving various disciplines to provide a comprehensive picture of the legal aspects of a legal relationship or legal event. Legal opinions have a significant position as a basis for thought that can contribute to legal progress and can take the form of criticism of certain policies. In order to have binding legal force.